2013
DOI: 10.1007/s11605-013-2148-y
|View full text |Cite
|
Sign up to set email alerts
|

Defining Postoperative Ileus: Results of a Systematic Review and Global Survey

Abstract: We have proposed standardised endpoints for use in future studies to facilitate objective comparison of competing interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
400
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(436 citation statements)
references
References 57 publications
7
400
2
10
Order By: Relevance
“…The clinical features of POI include nausea, vomiting, abdominal distension, inability to tolerate oral feeding, and delayed passage of flatus and stool. 3 Similarly, the clinical criteria used to define the resolution of POI are the passage of stool, return of flatus, absence of abdominal distension and pain, absence of nausea or vomiting, presence of bowel sounds, and tolerance of an oral diet. In our study, we assessed the resolution of POI by measuring GIT and stool weights, because judging levels of pain would be highly subjective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical features of POI include nausea, vomiting, abdominal distension, inability to tolerate oral feeding, and delayed passage of flatus and stool. 3 Similarly, the clinical criteria used to define the resolution of POI are the passage of stool, return of flatus, absence of abdominal distension and pain, absence of nausea or vomiting, presence of bowel sounds, and tolerance of an oral diet. In our study, we assessed the resolution of POI by measuring GIT and stool weights, because judging levels of pain would be highly subjective.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Previous studies have shown that POI lasts more than four days in more than half of the patients after major abdominal surgery, and it lasts for more than 6 days in 25%. 3 Although POI is not life-threatening, it involves additional medical cost and pain. Therefore, there has been much effort to reduce the severity and duration of the complication.…”
Section: Introductionmentioning
confidence: 99%
“…Gut immotility immediately postoperatively is an expected consequence of abdominal surgery (Vather et al 2013). There is a widespread belief that early ambulation assists in the resolution of gut immotility and prevention of paralytic ileus, yet there is no conclusive evidence to support this hypothesis (Story and Chamberlain 2009).…”
Section: Postoperative Paralytic Ileusmentioning
confidence: 99%
“…Primary outcome measures included average pain score on postoperative day (POD) 1-3, intravenous opioid requirement on POD 1-3, gastrointestinal recovery (time to tolerate solid diet and time to defecate), complication according to the Clavien-Dindo classification system [19] , prolonged postoperative ileus [20] , and length of postoperative stay. Pain scores were recorded every 4 h by nursing staff.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Once the oral intake exceeded 20 mL/kg body weight without nausea and vomiting, the diet was advanced to a low-residual solid diet. Prolonged postoperative ileus was defined as at least two times of nausea/vomiting, inability to tolerate oral diet and absence of flatus over 24 h, and abdominal distension with radiologic confirmation occurring on or after POD 4 [20] . Patients were discharged from the hospital when they had no fever, adequate pain control with oral analgesics, good ambulation, and satisfactory recovery of gastrointestinal function.…”
Section: Outcome Measuresmentioning
confidence: 99%